Integrated Traditional Chinese and Western medicine nursing and ward rounds based on medical-nursing integrated mode in a patient with heart failure (医护一体化模式下1例心衰病患者的中西医结合护理查房体会) - DING Lizhen (丁利祯); WANG Zhaojia (王兆嘉) (Association of Integrative Nursing, 2023)
This paper reviewed the experience of integrated Traditional Chinese and Western medicine nursing and ward rounds in a patient with heart failure, and evaluated the application of comprehensive interventions based on medical-nursing integrated mode. Intradermal needling therapy and health education under the concept of integrative medicine were carried out, demonstrating the worth of medical-nursing cooperation in clinical treatment and nursing of patient with heart failure. (本文回顾1例心衰病患者的中西医结合护理查房体会, 总结和评价医护一体化模式下护理干预在患者康复中的应用效果, 分享科室皮内针治疗及中西医结合健康宣教经验, 体现医护合作在心衰病临床治疗和护理中的应用价值。)